Kelalaian Negara dalam Perlindungan Hulu DAS Aceh: Analisis Sosio-Legal atas Banjir Bandang dan Kerusakan Hutan - William Andrew (Universitas Sains dan Teknologi Komputer, 2025)
The recurring flash floods in Aceh Province over the past decade demonstrate a strong link to deforestation in the upper reaches of the river basin. This condition reflects not only ecological issues, but also problems of governance, law, and state responsibility in environmental protection. This research aims to analyze the state's role and responsibilities in protecting the upstream watershed in Aceh and its connection to flash floods and forest damage. The research uses a qualitative approach within a socio-legal framework, employing a case study in Aceh. Data were obtained from in-depth interviews with key informants, limited field observations at the watershed's upper and lower reaches, spatial analysis of forest cover data, and a review of laws, policies, and official disaster reports. The research results indicate a reduction in forest cover in the upstream area of the watershed, which spatially overlaps with the downstream area experiencing recurrent flash floods. Empirical findings also show that although the legal framework for upstream watershed protection is available at the national and regional levels, management and supervision still vary in authority and are low-intensity in upstream areas. This research contributes to the development of socio-legal studies of environmental law by demonstrating that flash floods result from the interaction between ecological degradation and weak legal governance. In practice, this research confirms the importance of strengthening the state's role, institutional coordination, and upstream watershed monitoring as part of a sustainable disaster mitigation strategy.